Daseinsanálise como metódo hermenêutico-fenomenológico : por uma metapsicologia do existir - Santos, Ricardo Décio da Silva (2023)
This dissertation aims to develop and think about Daseinsanalysis as a metapsychology of existing. An existential philosophical look at psychic suffering and its therapy based on the phenomenological and hermeneutic methods from the existential-ontological aspects of the existential analytics of [dasein], presented by Heidegger in “Being and Time”. For this, it was tried to reconstruct the epistemological and ontological foundations of these methods, at the same time that it places the criticism on the problematic questions of the metaphysics of the traditional and modern ontology about the being of man, with the principles of existential aspects like understanding, interpretation, [epoché], intentionality, being-there, anguish. With this, it is intended to scrutinize the reception of existential analytics in the psychological sciences in the "Seminars of Zollikon" held by Heidegger in Switzerland, presenting a destructive reading of the sedimented horizon of meanings “nature, space, time, body”: with a view to releasing the phenomenological field to understand being-there as an opening of relationship in the world. Finally, it seeks to follow the work of the pioneers of psychiatric Daseinsanalysis, Ludwig Binswanger and Medard Boss, about crises and disorders through the phenomenon of dreaming, without referring to a “psychic” or “cerebral” instance, but emphasizing existence as a significant historical totality articulated by meaning. Besides that, this work Points out how the mode of [therapheia] can be shown in the care [sorge] of the relationship-with the other in a clinical ontic space, aiming to reach the possibility of an understanding of the Daseinsanalysis in contemporary times.